In Vitro Study of Mutagenicity and Genotoxicity of Some Bacterial Secretions associated with Bladder Tumors Tissues on Human Lymphocytes by Using Blood Tissue Culture Techniques - Al-Bayati, Avan H.; Guirges, Sami Y. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cytogenetic studies have been used to assess carcinogenic or mutagenic exposures and effects early in occupational, biological and environmental settings. Bacterial infection has not traditionally been considered asa major causes of cancer. Bacteria have been linked to cancer by two mechanisms: induction of chronic inflammation and production of carcinogenic bacterial metabolites. Objective: Because of new concepts in relating infection with certain malignancies the present study is performed. Therefore this study was conducted to determine the effects of bacterial products associated with biopsies of bladder tumor on human lymphocytes tissue cultures in vitro. Moreover, if there is any relation between these products for induction chromosomal aberration (CA) and formations of micronucleus (MN). Subjects and Methods: Chromosomal aberration and micronucleus assay were studied on six identified bacterial isolates of bladder tumor biopsies included 2 isolates of Escherichia coli , 2 isolates of Pseudomonas aeruginosa and 2 isolates of Klebsiella pneumoniae. The bacterial products activity for induction (CA) and (MN) were assayed according to the procedure mentioned in the text. Results: The results showed that each bacterial species have significant effects for induction different types of structural chromosomal aberration (CA) and formation of (MN). Conclusion: K. pneumoniae yielded high significant related predisposing factor in inducing different cytogenetic analysis followed by P. aeruginosa and E. coli .